2006
DOI: 10.1136/gut.2005.084574
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for association of OCTN genes and IBD5 with ulcerative colitis

Abstract: Background and aims: Genetic association between Crohn's disease (CD) and OCTN1 (SLC22A4) C1672T/OCTN2 (SLC22A5) G2207C variants in IBD5 has recently been reported. These genes encode solute carriers and the association was suggested to be distinct from the background IBD5 risk haplotype. There have been conflicting reports of the association between markers in the IBD5 region and ulcerative colitis (UC) and interaction (epistasis) between this locus and CARD15. Our aim was to ascertain the contribution of OCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 33 publications
(44 reference statements)
1
70
2
Order By: Relevance
“…This association has been subsequently replicated in a number of studies [61][62][63][64] , for both CD and UC [62,65] . Candidate polymorphisms found on this haplotype within the organic cation transporter OCTN1 (SLC22A4) and OCTN2 (SLC22A5) genes have been reported [66,67] .…”
Section: Ibd5 Association On Chromosome 5q31mentioning
confidence: 70%
“…This association has been subsequently replicated in a number of studies [61][62][63][64] , for both CD and UC [62,65] . Candidate polymorphisms found on this haplotype within the organic cation transporter OCTN1 (SLC22A4) and OCTN2 (SLC22A5) genes have been reported [66,67] .…”
Section: Ibd5 Association On Chromosome 5q31mentioning
confidence: 70%
“…These studies included diverse populations and originated from Canada [6,13,14], the UK [15][16][17][18], Germany [19], New Zealand [20], Spain [21], Italy [22,23], Belgium [24], Greece [25], Sweden [26] and Japan [27,28]. One Japanese and another Hungarian study with a small number of subjects found no association between OCTN 1&2 transporter polymorphisms and CD [28,29]; thus there could be ethnic differences in IBD5 locus mutations and propensity for Crohn's disease [7].…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that the immunomodulatory effects of ergothioneine may be beneficial, owing to inhibition of the atherogenic action of pro-inflammatory cytokines and adhesion molecules (41,42). Several SNPs of SLC22A4 were shown to be associated with chronic inflammatory disease, such as Crohn's disease, ulcerative colitis, rheumatoid arthritis and type 1 diabetes mellitus (43)(44)(45)(46). In the present study, rs273909 was associated with the prevalence of CKD but not to the serum concentration of creatinine or eGFR.…”
Section: Recessive Additive 1 Additive 2 ----------------------------mentioning
confidence: 47%